Correlation between disease knowledge and health related quality of life in patients with chronic obstructive pulmonary disease - Sushma; Sikka, Gitanjali; Singh, Pawan K.; Meetu (International Journal of Research in Medical Sciences, 2024)
Chronic obstructive pulmonary disease (COPD) is a growing global health concern, with approximately 10% of individuals over 40 affected by this debilitating condition. In India alone, an estimated 30 million people live with COPD. The disease significantly impairs health-related quality of life (HRQoL), with acute exacerbations leading to physical disability that limits daily activities and further deteriorates HRQoL. This study aims to assess the correlation between COPD knowledge and HRQoL among COPD patients, with specific objectives to evaluate the level of disease knowledge and HRQoL in this population. Patients’ awareness and understanding of COPD are critical for managing the disease effectively and maintaining a better quality of life. Treatment strategies must prioritize enhancing HRQoL by reducing exacerbations, improving lung function, and promoting smoking cessation. However, lower health literacy and insufficient knowledge about COPD are strongly associated with poorer HRQoL, increased disease severity, and a higher risk of hospitalizations and emergency department visits. Educational interventions focused on improving health literacy, particularly within COPD self-management programs, have the potential to significantly enhance HRQoL, decrease healthcare utilization, and improve medication adherence. This study underscores the importance of targeted education and self-management support in improving outcomes for COPD patients.